MITIGASI BENCANA SOSIAL DENGAN PENGUATAN MODERASI BERAGAMA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN - Widodo, Bali; Nugraha, Yogi (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2024)
The Indonesian nation is known as a pluralistic nation because it is built on the diversity of ethnicities, cultures, and religions. Plurality has the potential to give birth to social disasters in the form of horizontal conflicts in the name of religion. Therefore, it is necessary to find a learning strategy so that this can be minimized. This study aims to find out how much influence strengthening religious moderation in civic education learning can minimize the occurrence of social disasters. This research was carried out with a descriptive qualitative approach, this is to obtain a natural scientific picture of the phenomenon being studied. Data collection by conducting indirect observation through electronic media and library research methods where data is obtained from various previous research sources, articles relevant to the topic. Historical studies are also used in this study to look back at the national spirit that emerged before independence. The analysis of the discussion shows that strengthening religious moderation has a great impact on maintaining harmony in the midst of differences in beliefs among Indonesian people. The values of Pancasila, especially the precepts of God and Humanity, must be practiced in the attitude and behavior of every citizen in order to create a society that respects each other, understands each other, and lives in harmony as a nation in a country that is Baldatun Toyyibatun Warrobbun Ghafur.